Authoritarianism of Surfaces and Anti-Theoretical Ideologies. Considerations on Advanced Postmodernity - Gatto, Marco (International Gramsci Journal, 2025)
The essay explores the developments in cultural and literary theory over the last forty years, identifying adherence to postmodernity as its main direction. In particular, it discusses the transition from theory to a narrative form of theoretical discourse, the most obvious consequences of which are captured in a new logic of the surface that reveals genuine anti-theoretical temptations at work in a not insignificant part of contemporary thought.